Single molecule localization imaging of telomeres and centromeres using fluorescence in situ hybridization and semiconductor quantum dots. (11th May 2018) - Wang, Le; Zong, Shenfei; Wang, Zhuyuan; Lu, Ju; Chen, Chen; Zhang, Ruohu; Cui, Yiping
Abstract: Single molecule localization microscopy (SMLM) is a powerful tool for imaging biological targets at the nanoscale. In this report, we present SMLM imaging of telomeres and centromeres using fluorescence in situ hybridization (FISH). The FISH probes were fabricated by decorating CdSSe/ZnS quantum dots (QDs) with telomere or centromere complementary DNA strands. SMLM imaging experiments using commercially available peptide nucleic acid (PNA) probes labeled with organic fluorophores were also conducted to demonstrate the advantages of using QDs FISH probes. Compared with the PNA probes, the QDs probes have the following merits. First, the fluorescence blinking of QDs can be realized in aqueous solution or PBS buffer without thiol, which is a key buffer component for organic fluorophores' blinking. Second, fluorescence blinking of the QDs probe needs only one excitation light (i.e. 405 nm). While fluorescence blinking of the organic fluorophores usually requires two illumination lights, that is, the activation light (i.e. 405 nm) and the imaging light. Third, the high quantum yield, multiple switching times and a good optical stability make the QDs more suitable for long-term imaging. The localization precision achieved in telomeres and centromeres imaging experiments is about 30 nm, which is far beyond the diffraction limit. SMLM has enabled new insights into telomeres or centromeres on the molecular level, and it is even possible to determine the length of telomere and become a potential technique for telomere-related investigation.